Fabrication of layered In2S3/WS2 heterostructure for enhanced and efficient photocatalytic CO2 reduction and various paraben degradation in water. (May 2023) - Alhamzani, Abdulrahman G.; Yousef, Tarek A.; Abou-Krisha, Mortaga M.; Kumar, K. Yogesh; Prashanth, M.K.; Parashuram, L.; Hun Jeon, Byong; Raghu, M.S.
Abstract: Because of the excessive use of fossil fuels, CO2 emissions into the environment are increasing. An efficient method of converting CO2 to useful carbonaceous products in the presence of light is one way to address the issues associated with energy and environmental remediation. In2 S3 /WS2 heterostructure has been fabricated using the efficient hydrothermal method. The results of structural, morphological, optical, and photo/electrochemical characterization confirm the formation of a hierarchical, layered heterostructure of type-II. Enhanced photocatalytic activity is observed in InS/WS heterostructure compared to pristine In2 S3 and WS2 . InS/WS heterostructure exhibit higher photocatalytic activity than pure In2 S3 and WS2 . For 12 h, photocatalytic CO2 reduction produces 213.4 and 188.6 μmol of CO and CH4, respectively. Furthermore, the photocatalytic ability of the synthesized materials to degrade different parabens (Methyl: MPB, Ethyl: EPB, and Benzyl: BPB) under visible radiation was evaluated. Under optimized conditions, the InS/WS heterostructure degraded 88.6, 90.4, and 95.8% of EPB, BPB, and MPB, respectively, in 90 min. The mechanism of photocatalysis was discussed in detail. MCF-7 cell viability was assessed and found to exhibit low mortality in InS/WS treated MPB aqueous solution. InS/WS heterostructure could improve the fabrication of more sulphide-based layered materials to combat environmental pollution. Graphical abstract: Image 1 Highlights: Facile fabrication of layered In2 S3 /WS2 heterostructure. Improved exciton dissemination life-time in2 S3 /WS2 heterostructure. Efficient Photocatalytic CO2 reduction and Paraben degradation in water. Degradation pathway and mechanism discussed in detail. Toxicity assessment on MCF-7 cells was conducted in MPB treated water.